Genotypic-specific hormonal reprogramming and crosstalk are crucial for root growth and salt tolerance in bermudagrass (Cynodon dactylon) - Yang, Yong; Wassie, Misganaw; Liu, Ning-fang; Deng, Hui; Zeng, Yi-bing; Xu, Qian; Hu, Long-xing (Frontiers in Plant Science, 2022)
Salt stress is one of the major abiotic factors limiting the productivity of bermudagrass (Cynodon dacylon). However, the role of hormonal reprogramming and crosstalk in regulating root growth and salt tolerance in bermudagrass was not reported. Here, we examined the physiological and hormonal responses of two contrasting bermudagrass genotypes; 'C43', salt-tolerant 'C198' salt-sensitive. Under salt stress, 'C43' had better membrane stability and higher photosynthetic activity than the 'C198'. Salt stress promoted root growth and improved root/shoot ratio and root activity in 'C43', but the root growth of 'C198' was inhibited by salt stress, leading to diminished root activity. The two bermudagrass genotypes also showed critical differences in hormonal responses, especially in the roots. The root contents of indole-3-acetic acid (IAA), cytokinin derivatives, such as trans-zeatin riboside (tZR) and dihydrozeatin riboside (DHZR) were increased in 'C43', but decreased in 'C198' when exposed to salt stress. The root growth rate was positively correlated with the root IAA, tZR and DHZR, indicating their crucial role in root growth under salt stress. The expressions of TAA/YUCCA and CYP735A involved in IAA and tZR biosynthesis were induced by salt stress in 'C43', but inhibited in 'C198', leading to reduced hormone accumulations. Salt stress decreased the iP, tZ and DHZ content in the roots of both genotypes, and no significant difference was observed between the two genotypes. Salt stress reduced the content of GA3 in both genotypes by inhibiting GA20ox and GA2ox genes, which could be attributed to the reduced shoot growth in both genotypes. The increased ABA level by salt stress was significantly higher in 'C198' than 'C43'. Furthermore, there were positive and negative correlations between different hormones and root growth, suggesting that root growth could be regulated by complex hormonal reprogramming and crosstalk. This study provides a foundation for understanding the underlying mechanisms of hormonal-mediated root growth and salt tolerance in bermudagrass.